Students’ Errors in E-Learning Discussion in TEFL Course and Their Responses - Ni Made Ratminingsih; Made Hery Santosa; I Ketut Trika Adi Ana (Universitas Pendidikan Ganesha, 2022)
Lack of knowledge, practice, and forgetfulness can also contribute to typographical errors. Writing errors will impact the information presented and cannot be appropriately channeled. This research aims to analyze the types of mistakes made by students using English and identify their responses to the errors made. This type of research is qualitative. The research method is a qualitative descriptive method. The sample was determined purposively, namely students in class 3A who were categorized as having superior English skills among other classes. The methods used in collecting data are observation and interviews. The instrument used is a questionnaire sheet. The data analysis technique used is qualitative and quantitative analysis. The study's results proved that there were 7554 errors from 1875 conversations. 3332 (44.11%) lexical errors, 474 (6.27%) grammatical errors, and 419 (5.54%) spelling errors. Additional findings include grammar or mechanics errors, as much as 3329. (44%). Student responses varied towards the mistakes made, including limited knowledge, forgetting English grammar concepts, accustomed to thinking in the native language (mother tongue) or translating, lack of using tenses in everyday life, the assumption that one does not need to master grammar, and limited time and rush in writing answers, as well as lack of accuracy.